Clickbait, Rage Bait and The Contestation of Human Rights in Digital Public: A Comparative Study of Malaysia and Indonesia - Fauziah Hassan; Muhammad Raqib Mohd Sofian; Nurul Fathihin Mohd Noor Shah; Sofia Hayati Yusoff; Poppy Febriana (Jogjakarta Communication Conference (JCC), 2026)
The study conceptualises comment sections on social media platforms such as TikTok, Threads or Instagram and others as arenas where emotional expression intersects with civic reasoning and rights-based claims. Using a qualitative comparative content analysis, selected cases from Malaysian and Indonesian media accounts employing clickbait and rage-inducing narratives are examined. The analysis focuses on discursive patterns in user responses, including moral positioning, blame attribution, calls for accountability, rights assertions, exclusionary rhetoric, and polarised affective reactions. By comparing how digital publics engage with news stories involving rights related issues such as freedom of expression, religious sensitivities, and minority protections, the study explores whether emotionally charged raming fosters meaningful civic deliberation or intensifies antagonistic discourse. Through this comparative lens, the paper contributes to emerging scholarship on digital culture, civic engagement, and the evolving contestation of human rights in Southeast Asia.